Prosody of Focus among Information Structures in Pulaar - Mingzhen, Bao (AAeO - Afrikanistik-Aegyptologie-Online, 2012)
This paper presents preliminary results of an acoustic study of Futa Tooro, a dialect of Pulaar spoken in the region on the Senegal River. The study explores acoustic correlates of focused subjects, in comparison with unfocused subjects in information structures, in addition to the syntax and verb conjugation system. Focus in Pulaar is referred to as a constituent that introduces new or highlighted information into discourse and that potentially receives contrastive stress (McIntosh 1984). Declarative utterances are examined where subjects are read as nonfocus, informative focus as answers to Wh-questions and contrastive focus as corrections (i.e., negative answers) to Yes/No-questions. Acoustic parameters, such as duration, fundamental frequency and intensity, are examined in terms of focus condition, co-occurrence of emphasis particle ko, and completeness of sentence. The results show that contrastive focus is uttered with longer duration than informative focus and nonfocus subjects. Both contrastive and informative foci have greater intensity than nonfocus. Pitch modification is not significant for focus implementation. Moreover, foci preceded by ko and in complete long sentences have greater intensity than those without the particle or in incomplete short sentences. Examinations on time-normalized intensity and pitch contours indicate that when foci are realized with ko, pitch range is expanded in the focused position and compressed in the post-focal verb domain.